2023
DOI: 10.3389/fendo.2023.1133167
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial characteristical comparison reveals potential anti-aging function of Dubosiella newyorkensis in mice

Abstract: IntroductionPrevious study has indicated Dubosiella newyorkensis may act as a potential probiotic in age-related diseases. However, its detailed role in aging has not yet been promulgated. This study aimed to explore the potential anti-aging role of Dubosiella newyorkensis by comparing the anti-aging effect of resveratrol in young and old mice.MethodMeasurement of intestinal aging-related factors in colon and serum, and vascular endothelial function-related factors in serum were performed by enzyme-linked immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 41 publications
2
23
0
Order By: Relevance
“…27 The prominent strain Dubosiella inhabiting the intestinal tract can metabolize compounds to produce butyric acid, which possesses the beneficial effect of enhancing intestinal immunity and promoting host resistance to inflammation. 28,29 Akkermansia, recognized as a beneficial bacterium residing in the gut, has been linked to pathophysiological processes such as inflammation, obesity, and other disease states. 30−32 Importantly, studies employing pglyrp-deficient mice have demonstrated the colitis-protective characteristics of Alistipes, where it exerts mitigating effects on DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 The prominent strain Dubosiella inhabiting the intestinal tract can metabolize compounds to produce butyric acid, which possesses the beneficial effect of enhancing intestinal immunity and promoting host resistance to inflammation. 28,29 Akkermansia, recognized as a beneficial bacterium residing in the gut, has been linked to pathophysiological processes such as inflammation, obesity, and other disease states. 30−32 Importantly, studies employing pglyrp-deficient mice have demonstrated the colitis-protective characteristics of Alistipes, where it exerts mitigating effects on DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Increased abundance of Lachnoclostridium has been observed in patients diagnosed with ulcerative colitis and displaying inflammatory bowel lesions, establishing it as a potential microbial marker for the noninvasive detection of colorectal tumors and colon cancer . The prominent strain Dubosiella inhabiting the intestinal tract can metabolize compounds to produce butyric acid, which possesses the beneficial effect of enhancing intestinal immunity and promoting host resistance to inflammation. , Akkermansia , recognized as a beneficial bacterium residing in the gut, has been linked to pathophysiological processes such as inflammation, obesity, and other disease states. Importantly, studies employing pglyrp-deficient mice have demonstrated the colitis-protective characteristics of Alistipes , where it exerts mitigating effects on DSS-induced colitis . Furthermore, Lactobacillus has been identified as a key player in the inhibition of DSS-induced colonic inflammation in murine models, presumably through the activation of the AhR pathway, exhibiting regulatory functions on immune responses and nutrient metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…Each of these taxa have been previously identified as inversely associated with obese phenotypes [ 51 , 52 , 53 , 54 , 55 , 56 ]. The utility of these taxa in promoting metabolic health directly has been explored via probiotic potential; supplementation with D. newyorkensis has demonstrated improved endothelial function in mice [ 57 , 58 ], and clinical trials with A. muciniphila have shown improvement in markers of MetS including insulin sensitivity and hypercholesterolemia [ 11 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that interventions with beneficial substances can reshape the gut microbiota in colitis mice, leading to significant changes in certain bacterial genera [ 37 , 38 ]. In our study, we observed that compared to DSS-induced model mice, treatment with heat-killed S. boulardii increased the abundance of beneficial bacterial genera, including Dubosiella [ 39 ], Ligilactobacillus [ 40 , 41 ], Turicibacter [ 42 , 43 ], and Ileibacterium [ 44 ]. The growths of these genera were significantly suppressed in DSS model mice, indicating that heat-killed S. boulardii intervention can regulate the gut microbiota by restoring the abundance of dominant bacteria, thus achieving a new balance.…”
Section: Discussionmentioning
confidence: 99%